2017
DOI: 10.18203/2349-2902.isj20171515
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nebulized ketamine and ketamine with clonidine in postoperative sore throat

Abstract: Background: Postoperative sore throat (POST) consider a minor ailment in patients receiving general anesthesia with endotracheal intubation, seen in 21-65% cases but it causes significant distress and increases postoperative morbidity and patient dissatisfaction. This study was done to compare nebulized ketamine and ketamine with clonidine to treat POST.Methods: This was a prospective, randomized, double-blind control clinical study. After approval from institution ethical and scientific committee, study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Our results are comparable to a study by Jain et al in their nebulization group at 8 and 24hrs. 14 A study by Amingad, has shown fewer patients having no sore throat at 0 and 24hrs as compared to our study which could be attributed to the usage of 2% lignocaine local anaesthetic jelly applied over the endotracheal tube cuff and intra-operative i.v. dexamethasone used in their nebulized ketamine group.…”
Section: Discussionsupporting
confidence: 42%
“…Our results are comparable to a study by Jain et al in their nebulization group at 8 and 24hrs. 14 A study by Amingad, has shown fewer patients having no sore throat at 0 and 24hrs as compared to our study which could be attributed to the usage of 2% lignocaine local anaesthetic jelly applied over the endotracheal tube cuff and intra-operative i.v. dexamethasone used in their nebulized ketamine group.…”
Section: Discussionsupporting
confidence: 42%
“…In all, 15 studies reported that there were no systemic or local adverse events . One study reported that there were no differences in adverse events between topical ketamine and non‐analgesic methods .…”
Section: Resultsmentioning
confidence: 99%
“…Ketamine was topically administered as a single dose prior to surgery in all studies. Ketamine was administered as nebulization and gargle in 13 40,49,56,58,60,61,63,65,67,68,70,72,74 and 26 trials, [36][37][38][39][41][42][43][44][45][46][47][48][50][51][52][53]55,57,59,62,64,66,69,71,73,75,76 respectively, and in the other one, the endotracheal tube was lubricated with ketamine. 54 The dose of ketamine was fixed in 36 studies (50 mg, 23 studies 37,39,44,[48][49][50][51][52][53]…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations